The Role of Nurses and Paramedics in Laboratory-Based Epidemiological Surveillance: Enhancing Outbreak Detection and Response - Talal Abdullah Mohammed Alali; Fahad Suliman Ahmad Alhawiti; Bassam Abdullah Saleh Al Ahmadi; Asma Abdullah Abo shrian; Maram Suliman Mohammad Albalawi; Enas Abdullah Hussain Alali; Nawal Musalam Al.Hawaiti; Ahoed Aziz Alhwiti; Mariam ayad Alatawi; Maali Abdullah Alhawiti; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
In laboratory-based epidemiological surveillance, nurses and paramedics play a critical role in improving outbreak identification and response. Being on the front lines of healthcare, paramedics and nurses have special abilities that allow them to spot possible epidemics and help with prompt reporting to public health authorities. Beyond providing standard patient care, they play a crucial role in epidemiological surveillance by handling specimens, gathering clinical data, and keeping in touch with labs (Kumar et al., 2020).